PERGESERAN PELAKSANAAN UPACARA ADAT PERKAWINAN SUKU TIOCIU PADA MASYARAKAT TIONGHOA DI KELURAHAN PARIT TOKAYA KECAMATAN PONTIANAK SELATAN KOTA PONTIANAK - NIM. A1011191274, MARIA VIONITA (Jurnal Fatwa Hukum, 2023)
AbstractThe traditional marriage ceremony is one of the customs of the Chinese community in Pontianak City. The stages of the traditional wedding ceremony of the Chinese TioCiu tribe are proposal, determining the date and auspicious days, sangjit, decorating the bridal room and the procession of putting on bed linen, tea pie, wedding reception, returning home on the third day to the parents' house. The stages that shift are not determining an auspicious date and day, not returning to your parents' house on the third day after the wedding not decorating the bridal room, and not putting up bed linen. Formulation of the research problem "Is the TioCiu Tribe Traditional Marriage Ceremony in the Chinese Community in Parit Tokaya Village, South Pontianak District, Pontianak City Still Executed According to the Original Customs?". The purpose of this study was to obtain data and information regarding the implementation of traditional ceremonies, the causes and consequences of cultural shifts, and the traditional procedures for traditional TioCiu tribal marriage ceremonies. revealing the efforts of the Pontianak City Chinese Cultural Customs Council to the TioCiu ethnic Chinese community towards cultural preservation. The method used in this research is an empirical legal research method with a descriptive approach and qualitative analysis. The shift in the implementation of the traditional TioCiu wedding ceremony, namely the conditions used were not complete, did not choose an auspicious date and day, did not take part in the procession of installing bed linen, was not allowed to leave the house for three days and returned to the parent's house on the third day after the wedding. The implementation of the traditional wedding ceremony is still being carried out but has experienced a shift caused by economic factors, religious factors, educational factors, and modernization factors caused by technological advances. Legal consequences if customary violations occur, resulting in disruption of the magical balance. Efforts made by the Pontianak City Chinese Cultural Customary Council by providing directions and input so that they continue to carry out and preserve the culture and customs that have been passed down from generation to generation from their ancestors.Keywords: Ceremonies, Customs, Marriage, Chinese, TioCiu Abstrak Upacara adat perkawinan adalah salah satu adat pada masyarakat Tionghoa di Kota Pontianak. Tahapan upacara adat perkawinan masyarakat Tionghoa suku TioCiu adalah lamaran, menentukan tanggal dan hari baik, sangjit, menghias kamar pengantin dan prosesi pemasangan sprei, tea pai, resepsi perkawinan, pulang pada hari ketiga kerumah orang tua. Adapun tahapan-tahapan yang bergeser adalah tidak menentukan tanggal dan hari baik, tidak pulang kerumah orang tua pada hari ketiga setelah perkawinan dan tidak menghias kamar pengantin dan tidak memasang sprei. Rumusan masalah penelitian “Apakah Upacara Adat Perkawinan Suku TioCiu Pada Masyarakat Tionghoa Di Kelurahan Parit Tokaya, Kecamatan Pontianak Selatan Kota Pontianak Masih Dilaksanakan Sesuai Adat Aslinya?”. Tujuan penelitian ini adalah untuk mendapatkan data dan informasi mengenai pelaksanaan upacara adat, faktor penyebab dan akibat dari pergesaran budaya dan tata cara adat upacara adat perkawinan suku TioCiu. mengungkap upaya Majelis Adat Budaya Tionghoa Kota Pontianak kepada Masyarakat Tionghoa suku TioCiu terhadap pelestarian budaya. Metode yang digunakan dalam penelitian ini adalah metode penelitian hukum empiris dengan pendekatan deskriptif dan analisis kualitatif. Pergesaran dalam pelaksanaan upacara adat perkawinan suku TioCiu yaitu syarat yang digunakan tidak lengkap, tidak memilih tanggal dan hari baik, tidak mengikuti prosesi pemasangan sprei, tidak boleh keluar rumah selama tiga hari dan pulang kerumah orang tua pada hari ketiga setelah perkawinan. Pelaksanaan upacara adat perkawinan masih dilaksanakan namun mengalami pergeseran yang disebabkan oleh faktor ekonomi, faktor agama, faktor Pendidikan dan faktor modernisasi yang disebabkan oleh kemajuan teknologi. Akibat hukum jika terjadinya pelanggaran adat, sehingga mengakibatkan terganggunya keseimbangan magis. Upaya yang dilakukan oleh Majelis Adat Budaya Tionghoa Kota Pontianak dengan memberikan arahan serta masukan agar tetap melaksanakan dan melestarikan budaya dan adat istiadat warisan turun temurun dari para leluhur.Kata Kunci : Upacara, Adat, Perkawinan, Tionghoa, TioCiu